Using mixed models to describe growth in buffaloes (2011)
ABSTRACT: The objective of this study was to evaluate growth between 12 months and slaughter in 123 castrated male buffaloes. Body weight data, ultrasound, and bovimetric measurements were used. Linear mixed models of first and second order were used. The model included “lot” as a fixed effect. “Individual” and the three parameters of the model were included as random effects. The second order model had the best fit. “Lot” had a highly significant effect (p <0.01) for most of the traits. The βo values, estimated for body weight (BW), Ribeye area (REA), and rump fat thickness (RFT), were 184, 20.3, and 0.65, respectively. Monthly increments (β1) corresponded to 28, 44, 3.72, 1.25; and deceleration (β2) was -0.61, -0.116, -0.011, respectively. Measurements of height at the sacrum (HS) and height at the withers (HC) agreed with literature reports for this species. Chest circumference measurements (CC), body length (BL), separation between the ilia (II), and distance between ilium-ischium (IIS) were lower than those reported in the literature. Buffalo growth was well described by the quadratic model. This model fits better the growth curve for buffaloes when random parameters are included. During the study, animals maintained the normal physiological behavior described for cattle growth.